Propulsive techniques: Front crawl stroke, butterfly, backstroke and breaststroke - Schleihauf, R. E.; Higgins, J. R.; Hinrichs, R. (Swimming Science V, 1988)
This article includes a hand propulsive force analysis of 12 female and 14 male swimmers from the 1984 U.S. Olympic team. Summary statistics of pulling motion and hand propulsive forces are presented in each of the four competitive strokes. Further, a detailed example of model stroke technique is presented for one subject in each stroke to clarify the relation between pulling motion, hand angle of pitch, and propulsive force.